Respiratory dysbiosis as prognostic biomarker of disease severity for adults with community-acquired pneumonia requiring mechanical ventilation - Loreto Vidaur; Amalur Guridi; Oihana Leizaola; Jokin Marin; Jordi Rello; Cristina Sarasqueta; Ane Sorarrain; Jose María Marimón (Pneumonia)
Abstract Objetives To ascertain the role of the lung microbiome in the development of severe pneumonia and its potential as a biomarker for disease progression. Methods BAL samples from 34 adults with severe community-acquired pneumonia (CAP) (17 viral, 8 viral coinfected with bacteria and 9 bacterial) admitted to the ICU for acute respiratory failure between 2019 and 2021 were collected within the first 48 h of admission to the ICU. The microbiome was characterized via the Ion 16S Metagenomics Kit and the Ion Torrent sequencing platform. Clinical factors, including survival, mechanical ventilation duration, blood biomarkers and organ failure in terms of acute respiratory distress syndrome (ARDS), shock or acute renal failure, were correlated with microbiome characteristics. Results The microbiome diversity in patients with viral pneumonia was significantly greater than that in patients with bacterial or coinfected pneumonia: the Shannon diversity index was 3.75 (Q1–Q3: 2.5–4.1) versus 0.4 (Q1–Q3: 0.2–1.3) and 0.48 (Q1–Q3: 0.3–1.1), respectively (p < 0.05). The microbiome diversity index was associated with severity-of-illness (APACHE II), independent of the etiology of pneumonia (B coefficient -1.845; p < 0.01). Patients with severe viral CAP who developed ARDS had a lower presence of Proteobacteria, and those who were complicated with ventilator-associated pneumonia had a higher prevalence of Acinetobacter at admission. The mortality of patients with bacterial or coinfected pneumonia was 35%. In coinfected patients, the diversity index was associated with the development of shock. Conclusion Patients with severe CAP have low respiratory microbiome diversity, indicating that respiratory microbiome diversity is a potential biomarker of disease severity.